Hereditary angioedema (HAE) in Belgium: results from a national survey - Van der Poorten, MM; Schrijvers, R; Hermans, C; Bartiaux, M; Haerynck, F; Lapeere, H; Moutschen, M; Michel, O; Sabato, V; Ebo, DG; Van Gasse, AL (Frontiers in Allergy, 2023)
Background Hereditary angioedema (HAE) is a rare heritable disorder that is characterized by recurrent, circumscribed, nonpitting, nonpruritic, often painful subepithelial swellings of sudden unpredictable onset that generally fade during 48–72 h. Epidemiological data of hereditary angioedema patients in Belgium is lacking. Methods We set up a nation-wide, multicentric study involving the 8 Belgian hospitals known to follow-up patients with Type I and II HAE. All Belgium HAE patients were asked to fill out questionnaires that mainly covered demographic data, family history, and detailed information about diagnosis, treatment and burden of their Type I and II HAE. Results 112 patients with type I or type II HAE could be included. Median delay between first symptoms and diagnosis was 7 years. 51% of patients had experienced pharyngeal or tongue swelling and 78% had experienced abdominal symptoms, both known to cause an important reduction in quality of life. 60% of symptomatic patients reported to receive long term prophylactic treatment. Human plasma-derived C1-esterase inhibitor concentrate was used by 56.3% of patients. 16.7% and 27.1% of patients used a 17-α-alkylated androgen and tranexamic acid as long term prophylactic therapy. Conclusions We present the first nation-wide epidemiological study regarding HAE in Belgium. Our data show that the morbidity of HAE is not to be underestimated. Knowledge and dissemination of this data is critical in raising awareness, encouraging development of therapies and optimising nationwide management.